Psychological coping skills in brazilian athletes Habilidades psicológicas de coping em atletas brasileiros - Coimbra D.R. (2013)
The aim of the present study was to analyze the coping skills in Brazilian athletes. Specifically, verify the differences between the genders (male and female), sports (individual and collective), at different levels (regional, national and international). The sample was 375, mean age 16.8 ± 2.1, mostly male (74.7%) and sports collective (68.3%). Concerning level, 124 athletes were rated regional level, 72 national level and 171 international level. The instrument used was the Coping Skills Inventory-28 (ACSI-28), Brazilian Portuguese version (ACSI-28BR) with items specific coping skills in the sport. Significant difference for main effect in the interaction between gender, sport and competitive level for: Coping with adversity and peak under pressure. The study found that different contexts directly influence the acquisition of coping skills. © FTCD/FIP-MOC.